Employment Status of Women in Tourism at Pokhara, Nepal - Sharma, Laxmi Kanta (Journal of Development and Administrative Studies, 2017)
The employment generation from Pokhara as an established tourism destination in Nepal carries special significance in evaluating economic impact. This study aims to explore female employment status and influencing factors for the participation of women in tourism at Pokhara. A total of 250 respondents were sampled from ten tourism enterprises and ten in-depth interviews were conducted in order to gather primary data. Demographic factors such as age and marital status; socio-economic factors like educational level, work environment have been identified as independent variables that might have effect on women’s level of participation. The findings reveled that women’s participation in managerial position is low (31%) comparing to the operative level (69%). About 75 percent of employed women are moderately satisfied indicating the urgent need of improvement in working environment. The percentage of women employment lies only between minimum 20 to maximum 45 percent indicating the urgent need of trainings and skill development on women. The training on women has been found a noteworthy impacting factor for employment creation. The outcome of the study has positive implication on policy formulation for women employment in tourism sector.